2014
DOI: 10.1086/676826
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-dynamics of Hypoxia and Fisheries: The Case of Gulf of Mexico Brown Shrimp

Abstract: We analyze the Gulf of Mexico brown shrimp fishery and the potential impacts of a large seasonal area of hypoxia (low dissolved oxygen) that coincides with the peak shrimp season.A spatial-dynamic bioeconomic simulation embeds three biological impacts on shrimp: mortality, growth, and aggregation on hypoxic edges. Hypoxia creates feedbacks in the bioeconomic system, altering catch and effort patterns. System changes propagate over space to affect areas that do not experience hypoxia. Areas that might otherwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Effort response to profitability creates feedbacks between the human (fishing fleet) and natural (shrimp population) systems that undermine quasi-experimental approaches to observational data (10,21). When an area becomes hypoxic, the increased catchability along the edge draws fishing effort into the area and away from nonhypoxic areas (12)(13)(14), changing the fishing effort in both places relative to the counterfactual.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effort response to profitability creates feedbacks between the human (fishing fleet) and natural (shrimp population) systems that undermine quasi-experimental approaches to observational data (10,21). When an area becomes hypoxic, the increased catchability along the edge draws fishing effort into the area and away from nonhypoxic areas (12)(13)(14), changing the fishing effort in both places relative to the counterfactual.…”
Section: Resultsmentioning
confidence: 99%
“…Within the region most affected by hypoxia, these correlations are weaker and suggest negative effects on large shrimp and positive effects on small shrimp (SI Appendix, Table S2). Because establishing a causal effect of hypoxia requires a valid counterfactual, aggregate fishery landings are insufficient because so many environmental, economic, and institutional factors influence fishery outcomes (3,10,17,18). Economic studies of other, smaller fisheries have found modest economic losses from hypoxia (17)(18)(19)(20).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…There are other pathways by which hypoxia could affect croaker population dynamics that were not included in our model simulations. For example, hypoxia avoidance can lead to changes in overlap of croaker and their predators (see Ludsin et al 2009), hypoxia exposure can reduce sperm production by males (Thomas and Rahman 2010), and shifts in shrimp fishery in response to hypoxia (Smith et al 2014) can affect croaker mortality via bycatch. These additional effects can be added to the model simulations (e.g., predation from habitat compression- Adamack et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have incorporated environmental externalities into bio-economic models of fisheries (Barbier and Strand, 1998;Simonit and Perrings, 2005;Foley et al, 2009;Udumyan et al, 2010;Foley et al, 2012;Nguyen et al, 2013;Smith et al, 2014;Nguyen et al, 2015). Barbier and Strand (1998) study the effect of changes in mangrove areas on the carrying capacity of shrimp stocks in Mexico, while Simonit and Perring (2005) look at effects of eutrophication on growth of fish in Lake Victoria.…”
Section: Background and Purposementioning
confidence: 99%